Translation and cross-cultural adaptation of the Nepali version of the International Consultation on Incontinence Questionnaire-Urinary Incontinence Short Form - Khadgi, Bimika; Stensdotter, Ann-Katrin; Acharya, Ranjeeta Shijagurumayum; Brandt, Corlia; Stuge, Britt (Journal of Nepal Health Research Council, 2024)
ABSTRACTBackground: The International Consultation on Incontinence Questionnaire Urinary Incontinence Short Form (ICIQ-UI SF) is a questionnaire for evaluating the frequency, severity, and impact on quality of life of persons with Urinary incontinence. Urinary incontinence is a stigma, and a Nepali version of the ICIQ-UI SF will help to screen for incontinence, and be valuable for clinicians, researchers, and for persons with urinary incontinence.Methods: After receiving ethical clearance and permission from ICIQ, the translation and cross-cultural adaptation was conducted using the ICIQ module protocol. This incorporated initial translation of the questionnaire, backward translation with involvement of ICIQ. The necessary adjustments were made during a meeting with the reconciliation expert team. After the approval from the ICIQ, interviews were conducted with eight women with urinary incontinence for conceptual equivalence. After cognitive debriefing, the comments were checked and proofreading of the questionnaires for comprehensibility, readability and accuracy of the grammar were done. Final typesetting and formatting were checked to match the original ICIQ-UI SF.Results: The IICIQ-UI SF was successfully translated and cross-culturally adapted while maintaining the characteristics of the original source.Conclusions: Through translation, review from the experts and interviews conducted with Nepalese women experiencing urinary incontinence, a relevant and comprehensive ICIQ-UI SF was developed to use in Nepal. The questionnaire will be of great value for clinical use and future studies involving Nepalese women.Keywords: Linguistic translation; Nepal; outcome measure; urinary incontinence; women's health.